Antiproliferative effect of hydroalcoholic brown propolis extract on tumor and non-tumor cells - I. Vendruscolo; G. H. Berton; M. T. Biffi; P. A. Bressiani; A. K. G. Oliveira; A. P. Berti; V. M. Concato-Lopes; W. R. Pavanelli; A. P. Simon; T. L. C. Oldoni; F. A. R. Santos; I. A. L. Dalmolin; et al. (Brazilian Journal of Biology)
Abstract Studies show that propolis has antimicrobial, antifungal, antiviral, anti-inflammatory, antioxidant, antitumor, and immunomodulatory properties, and may protect against diseases such as diabetes, cardiovascular disease, and cancer. We aimed to extract compounds of brown propolis with hydroalcoholic solvents and evaluate their cytotoxic activity on tumor and non-tumor cells by MTT test. We tested the solute:solvent ratio (ethanol:water) and extraction time in a Shaker incubator (710 rpm) before conducting a central composite rotational design (CCRD) to optimize time and solvent mixture. We found that a temperature of 80 °C and a solvent concentration of 90:10 were the best extraction conditions for phenolic compounds, especially pinocembrin and cinnamic acid. The extract showed antioxidant capacity, acid characteristics, low humidity, and the presence of ash, lipids, and soluble solids. The cytotoxicity test with normal kidney cells of Macaca mullata (LLC-MK2) and human lung tumor cells (A549) showed no statistical difference from the negative control. For liver tumor cells (HuH7.5), different concentrations showed cytotoxic/antiproliferative activity. Thus, the data indicate that this product deserves prominence in the search for new applications.